#$&*
course MTH 279
2:33 pm 2/28
Query 07 Differential Equations
*********************************************
Question: 3.4.2. Solve the equation y ' = 2 t y ( 1 - y), with y(0) = -1, as a Bernoulli equation.
YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY
Your solution:
v = y^(1-n)= y^-1
v' + (-1)2tv = -2t
I= e^-t^2
e^(-t^2)*v = int(-2te^(-t^2)) = e^-t^2
v = 1 + Ce^(t^2)
y= v^(1/-1) = v^-1
y = (1+Ce^(t^2))^-1
y = 1/(1+Ce^(t^2))
y(0)= - 1 --> C = -2
y = 1/(1-2e^(t^2))
confidence rating #$&*:
^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
.............................................
Given Solution:
&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&
Self-critique (if necessary):
------------------------------------------------
Self-critique rating: